A combination of quinidine/mexiletine reduces arrhythmia in dilated cardiomyopathy in two patients with R814W SCN5A mutation. (20th October 2020) - Zakrzewska‐Koperska, Joanna; Bilińska, Zofia T.; Truszkowska, Grażyna T.; Franaszczyk, Maria; Elikowski, Waldemar; Warmiński, Grzegorz; Kalin, Katarzyna; Urbanek, Piotr; Bodalski, Robert; Orczykowski, Michał; Szumowski, Łukasz; Płoski, Rafał; et al.
Abstract: SCN5A gene mutations are described in 2% of patients with dilated cardiomyopathy (DCM) and different rhythm disturbances, including multifocal ectopic Purkinje‐related premature contractions. Recent data indicate that sodium channel blockers are particularly effective monotherapy in carriers of the R222Q SCN5A variant. Our purpose is to describe the effectiveness of antiarrhythmic treatment in a family with genetically determined arrhythmogenic DCM associated with the R814W variant in the SCN5A gene. We examined a family with arrhythmogenic DCM (multifocal ectopic Purkinje‐related premature contractions phenotype, atrial tachyarrhythmias, automatism, and conduction disorders) and described antiarrhythmic treatment efficacy in heart failure symptoms reduction and myocardial function improvement. We found a heterozygotic mutation R814W in SCN5A by whole exome sequencing in the proband and confirmed its presence in all affected subjects. There were two sudden cardiac deaths and one heart transplantation among first‐degree relatives. The 58‐year‐old father and his 37‐year‐old daughter had full spectrum of symptoms associated with R814W SCN5A mutation. Both had implanted cardioverter defibrillator. In the father, adding mexiletine to quinidine therapy reduced ventricular arrhythmia (50–60% → 6–8% of whole rhythm) and reverted long‐standing atrial fibrillation to sinus rhythm. In the daughter, mexiletine and overdrive pacing were effective in ventricular arrhythmia reduction (25% → 0.01%). Because of a growing number of atrial fibrillation recurrences, a reduced dose of quinidine (subsequently flecainide) was added, resulting in arrhythmia significant reduction. In both cases, antiarrhythmic effectiveness correlated with clinical improvement. In SCN5A R814W‐associated DCM, a combination of Class I antiarrhythmics and overdrive pacing is an effective treatment of severe ventricular and atrial arrhythmias.